Peran Local Strongman Dalam Gerakan Penolakan Tambang dan Kontestasi Pemilukada di Kabupaten Mandailing Natal 2010-2015 - Rozak, Abdul - (Jurnal Review Politik, 2019)
Geothermal mining activities have caused open conflict in the community. On one hand the community accepts the company's presence and on the other hand refuses with the assumption of damage to nature and the social environment. The anti-mining community made a social movement by forming a strong organization and becoming a dominant social group with a series of incentive offers and sanctions for anyone in the mining area. The social movement gave birth to the phenomenon of strong soceity and weak countries driven by local strongmen who succeeded in forcing the government to revoke mining licenses and win one pair of candidates in the election contestation in the main mining area. This article will describe and analyze the phenomenon of strong society and weak state and the role of local trongman in the social movement of mining rejection and local election contestation.